2012
DOI: 10.3390/mi3020255
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Vibrations of Thermally Actuated Silicon Membranes

Abstract: Abstract:A thermally-actuated micro-electro-mechanical (MEMS) device based on a vibrating silicon membrane has been proposed as a viscosity sensor by the authors. In this paper we analyze the vibration mode of the sensor as it vibrates freely at its natural frequency. Analytical examination is compared to finite element analysis, electrical measurements and the results obtained through real-time dynamic optical surface profilometry. The vertical movement of the membrane due to the applied heat is characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The movement of the membrane is measured through a Wheatstone bridge of boron-implanted p+ silicon piezoresistors. During normal operating conditions, the center of the membrane has been shown to be displaced by ~120 nm when an instant power of 4 Watts is applied [29,30]. The driving and amplification circuitry are described in detail in [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement of the membrane is measured through a Wheatstone bridge of boron-implanted p+ silicon piezoresistors. During normal operating conditions, the center of the membrane has been shown to be displaced by ~120 nm when an instant power of 4 Watts is applied [29,30]. The driving and amplification circuitry are described in detail in [29].…”
Section: Resultsmentioning
confidence: 99%
“…These include the CVD-based Parylene-C [20][21][22][23][24][25], silicone-based coating, and other polymers [26][27][28]. Even though these have been proven effective at protecting packaged electronics and components placed on a PCB [28][29][30][31], few studies have shown their effectiveness when protecting actuators embedded in the sensing environment [25].…”
Section: Introductionmentioning
confidence: 99%